Efektivitas Model Pembelajaran Contextual Teaching And Learning Dalam Meningkatkan Hasil Belajar Sejarah - Isbandiyah Isbandiyah; Sarkowi Sarkowi; Rohana Rohana (Kaganga:Jurnal Pendidikan Sejarah dan Riset Sosial Humaniora, 2020)
The research aims to analyze effect of the Contextual Teaching and Learning model on history learning outcomes at SMK Negeri 1 Lubuklinggau and analyze effectiveness of the Contextual Teaching and Learning model in improving history learning outcomes at SMK Negeri 1 Lubuklinggau. The type of research is a pure experimental research with used pretest-postest group design. The sample the students at X AKL3 as the experimental class with the students X X AKL1 as the control class. The result of data analysis in this research concluded that: (1) Contextual Teaching and Learning model affect the history learning outcomes at SMK Negeri 1 Lubuklinggau; and (2) Contextual Teaching and Learning model are affective in improving the history learning outcomes at SMK Negeri 1 Lubuklinggau. Keywords: history learning outcomes, Contextual Teaching and Learning model (CTL)